Analysis and Remedies for Factors Responsible for Time Between Overhaul: A Case Study of DO-228 Aircraft Starter Generator (Nigerian Journal of Technology, 2022)
The starter generator is used for cranking the engine and to produce electricity for the aircraft system after a sustainable speed.A review of relevant literature reveals the time between the overhaul of the Do-228 aircraft starter generator but did not go in-depth to unravel the factors responsible. A survey research method is adopted to elicit information on the factors. Raosoft sample technique calculator: a software that primarily calculates or generates the sample size of a research or survey was used to obtain the minimum sample size from the study population with the nominal rolls of the technicians as the sampling frame. The questionnaire was vetted and validated by a professional focus group discussion team. The result shows that the factors responsible for the time between overhaul of the starter generator are Environmental Factors (10%), Mechanical Factors (20%), Poor Maintenance Factors (17%), Time Due (25%), Usage/Life Cycle (16%) and Aging (12%). 75% overhaul is unscheduled. It is recommended that the overhauling of the aircraft starter generators be done at 900 as against 1000 flight hour intervals to mitigate unscheduled maintenance.